Post‐quantum cryptography techniques for secure communication in resource‐constrained Internet of Things devices: A comprehensive survey. (11th July 2022) - Kumari, Swati; Singh, Maninder; Singh, Raman; Tewari, Hitesh
Abstract: As the number and characteristics of smart devices change, the concept of the Internet of Things (IoT) emerges. The IoT provides the connected devices with a variety of resources that enable effective communication. At this point, several security issues arise to get the sensitive information behind every communication in the IoT. To provide users with security and privacy, cryptographic schemes are adopted, the most popular being public key cryptographic systems (PKC). However, with the advent of quantum computing, the level of security that can be provided by the PKC schemes is a big question. Another important issue is that the IoT environment is resource‐constrained, which necessitates the implementation of lightweight cryptographic algorithms for better security. In response to these issues, the post‐quantum cryptographic (PQC) schemes are one of the significant developments contributing to IoT security in the post‐quantum world. This article examines the key security issues in the IoT environment and examines the effective solutions found in the literature. The problems in IoT in the quantum era are discussed and appropriate solutions by PKC schemes under limited resources in IoT are focused. As the lattice‐based cryptosystems are more effective, the importance of these schemes in the resource‐constrained IoT is highlighted. This survey also leads to feasible future directions that can support developers and researchers in this field.